The bully, the bullied, and the bystander : from pre-school to high school : how parents and teachers can help break the cycle of violence - Coloroso, Barbara (New York : HarperCollins, 2003)
Describes in detail, the common attributes of those who bully, those who are bullied and those who stand by while abuse happens and what can be done to educate our children about bullying and it's consequences.
Includes bibliographical references and index.
Keywords: School violence -- Prevention; Bullying -- Prevention; USA